Analysis of the composition of tantalum nitride in CMOS metallization trenches using parallel angle‐resolved XPS. (4th October 2020) - Wehring, Bettina; Gerlich, Lukas; Kia, Alireza M.; Wislicenus, Marcus; Uhlig, Benjamin
Abstract : We demonstrate the utilization of parallel angle‐resolved X‐ray photoelectron spectroscopy (pAR‐XPS) as a useful tool to analyze ultrathin sputtered tantalum nitride (TaN) thin films in complementary metal‐oxide‐semiconductor (CMOS) trenches. The chemical composition of TaN was estimated by pAR‐XPS using a Theta 300i from Thermo Fischer. An improved lateral resolution was achieved by analyzing periodic structures. The XPS data was correlated with transmission electron microscopy (TEM) in combination with energy‐dispersive X‐ray spectroscopy (EDX) and time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) data. The results show that the nitrogen content in the TaN thin films was about 6% higher at the sidewall compared with the top and bottom of the trench.